(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: This study aims to explore the prevalence of depression among drug-resistant tuberculosis (TB) patients in Vietnam. A total of 250 patients were sampled, utilizing the PHQ- 9 questionnaire to assess levels of depression, along with gathering personal characteristics including age, geographical location, occupation, and treatment frequency. Methods: This quantitative study employed questionnaires and descriptive statistical analysis to identify depression levels and related factors. Results: Findings indicate that 34.4% of patients did not experience depression, whereas 36.8% suffered from mild depression and 14% from moderate depression. A significantly increased level of depression was observed in individuals who had a history of forgetting to take their TB medication (OR = 0.5; p = 0.032) and in the low-performing knowledge group with a high rate of depression (70.2%). Discussion: The research underscores the importance of screening and intervening for depression among drug-resistant TB patients, especially those with a history of non-compliance with treatment. Enhancing psychological support and timely intervention can improve the quality of life and treatment outcomes for TB patients.